Quality assurance for dynamic tumor tracking - Witulla, Barbara; Ziegler, Marc; Brandt, Tobias; Prasetio, Heru; Fietkau, Rainer; Bert, Christoph (Zeitschrift für Medizinische Physik, 2021)
The purpose of this work was to develop a treatment plan verification routine for a linear accelerator dedicated to SBRT treatments with gimbal based dynamic tumor tracking using three commercially available phantoms. The accelerator system has two special features: It operates with a rotation of the ring shaped gantry instead of a couch rotation and target motion can be compensated for via a gimbal system (dynamic tumor tracking, DTT). DTT plans were each measured with the three different phantoms. Afterwards the measured dose distribution was compared with the calculated dose distribution via global Gamma Index analysis (3 mm / 3%, threshold: 10%). The global gamma pass rates were on average (93.5 ± 7.2) % for ArcCHECK, (98.0 ± 2.6) % for OCTAVIUS® 4D and (98.4 ± 4.2) % for MatriXX Evolution. All three systems could be used for quality assurance with ring rotations and DTT, however, each with limitations.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Intensity modulated radiation therapy; quality assurance; Stereotactic body radiation therapy; Tumor Tracking